If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-7x + 8) = -483 Reorder the terms: 7(8 + -7x) = -483 (8 * 7 + -7x * 7) = -483 (56 + -49x) = -483 Solving 56 + -49x = -483 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -49x = -483 + -56 Combine like terms: 56 + -56 = 0 0 + -49x = -483 + -56 -49x = -483 + -56 Combine like terms: -483 + -56 = -539 -49x = -539 Divide each side by '-49'. x = 11 Simplifying x = 11
| 12x+23=71 | | x^3=167 | | 17.00+5.50h=11.00+6.75h | | 98=7x-7 | | 4y-5y=81 | | 10+4c=5(c-6)+33 | | 5+(-24)= | | 2.5d+7.75=4+3.25d | | 6(x+3)-4(x-3)= | | 3w^2(w^2+3)=8+7w^2 | | 13x+2=54 | | 835=5x^3 | | 360=106+84+y+38+3y+12 | | 5+7*5+5= | | 4x-8=4x+-36 | | 4d=9-d-8 | | 5+2*5+5= | | -2(-4+x)=20 | | 2x+2=6x-10 | | 6log(x)=9 | | m=15C+10 | | 29=8x-11 | | 166=4n | | 3(2x+6)+4x=38 | | 13+7=z | | 4x-3x+2x-3+5x= | | 10y+1.5y=7(1.5y)+y | | 3(2x+6)+4x=3 | | -7x+(-14)=28 | | 4p^2+13p=2-4p^2-2p | | -12=2p | | 7x+y=10y+x |